A face in the crowd - King, Stephen, 1947-; O'Nan, Stewart, 1961-; Chizmar, Richard, 1965- (Cemetery Dance Publications, 2023)
In "A Face in the Crowd," widower Dean Evers sees faces from his past while watching baseball; and in "The Longest December," the Howard family struggles to see their kind and gentle neighbor James Wilkinson as the violent criminal the police are investigating.